KEMAMPUAN MENDENGARKAN DENGAN MODALITAS AUDITORI BERBASIS GENDER - Cunandar, Dadang (Universitas Muhammadiyah Surakarta, 2019)
This article aims to (1) describe the characteristics of gender based auditory learning modalities, (2) to investigate the supporting aspects of the students’ listening abilities, and (3) to tell the students’ abilities to listen to gender-based texts. This research implements qualitative approach and study case methods. The subject includes fifth grade students of Cigugur state school V. The data was collected through literature studies, observation, interviews, documentation, and fieldnotes. The validity of the data is checked through the data credibility and dependability. The data were analyzed with a reduction of the data, data description, and conclusions. The characteristics of male students’ stereotype is showing an independent character, strong personality, and ambitious. The stereotype for female students includes cheerful, spoiled, and obedient. The supporting aspects for the listening abilities include physical aspect, psychological aspects, gender, and media. In addition, the listening ability of the female students are considered more advanced. Keywords: listening abilities, gender